Health care-resource utilization before and after natalizumab initiation in multiple sclerosis patients in the US - Bonafede MM; Johnson BH; Watson C (Dove Medical Press, 2013)
Machaon M Bonafede,1 Barbara H Johnson,1 Crystal Watson2 1Truven Health Analytics, Cambridge, MA, USA; 2Biogen Idec, Weston, MA, USA Objectives: To evaluate multiple sclerosis (MS)-related health care-resource utilization and costs prior to and after initiating natalizumab in the US. Materials and methods: A retrospective administrative claims analysis was conducted using the Truven Health MarketScan Databases to identify adults diagnosed with MS who initiated natalizumab (index date) between January 1, 2007 and December 31, 2010. Patients had ≥24 months of continuous enrollment (12 months before [preperiod] and 12 months after [postperiod] the index date) and remained on natalizumab for the 12-month postperiod. Patients with and without other disease-modifying treatment (DMT) during the preperiod were examined. Patient characteristics, MS-related inpatient stays, and corticosteroid use were compared in the pre- and postperiods using paired statistical tests, where appropriate. Results: The study comprised 1,458 patients, mean age 45.2 years (standard deviation 10.5), 74.2% female. The majority (70.3%) used a DMT during the preperiod. After initiating natalizumab, there was a significant reduction in the percentage of patients with MS-related inpatient stays (7.6% versus 2.4%, P<0.001), MS-related inpatient costs (median US $12,078 versus US $9,784, P<0.001), and length of stay (7.12 days versus 6.26 days, P=0.005). Both cohorts showed a reduction in the percentage of patients with MS-related inpatient stays and costs with greater reductions for patients without DMTs in the preperiod (–6.2% [P<0.001] and –US $1,496 [P=0.056], respectively) compared to those with a DMT in the preperiod (–4.8% and –US $1,262, respectively, P<0.001 for both). Compared to the preperiod, there were significant reductions in intravenous and oral corticosteroid use for natalizumab initiators (–60.1% and –52.9%, respectively, P<0.001 for both). These utilization reductions correspond to mean corticosteroid cost-per-patient reductions of –US $101 across all natalizumab users (P<0.001). Conclusion: The initiation of natalizumab was associated with significant decreases in MS-related inpatient stays, and corticosteroid use with corresponding decreases in length of stay and costs among natalizumab users with and without DMTs in the prior year. Keywords: multiple sclerosis, natalizumab, health care-resource utilization, health care costs